INTRODUCTION TO GASTRODIPLOMATION OF ASEAN MEMBER STATES TO STUDENTS OF SMKN 30 JAKARTA THROUGH WEBINAR ACTIVITIES WITH THE MINISTRY OF FOREIGN AFFAIRS - Muhammad Kevin Muhfly Alfath; Muhammad Kholid Alfina (Sean Institute, 2023)
Gastrodiplomation is a word adopted from Gastronomy that does not have a similar meaning and meaning to culinary. The government in every country created an official program to introduce its domestic cuisine to the international world through diplomacy. Currently, culinary is one of the important factors in attracting the attention of the world community to travel to various countries, in the current era of globalization information about the culinary of a country it is very easy and fast to access, from a wide variety of social media platforms such as Instagram, Facebook, Twitter and so on. With this phenomenon, we held community service activities to introduce gastrodiplomation to students in Indonesia, especially in the Jakarta area because Jakarta as The capital city of the Republic of Indonesia, students must know that this activity is one of the diplomatic activities, namely gastrodiplomation. We held a webinar,